Peran Gerbang dan Tembok Penyengker Rumah Vernakular Bali dalam Pengendalian Kebisingan Ruang Luar - I Gusti Ayu Agung Manik Prihartini; Ima Defiana; Dewi Septanti (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
Apart from functioning as a barrier to houses and other properties, gates can also function as a noise barrier. The gates in Balinese vernacular houses have various typologies and are equipped with locking walls which can act as a noise barrier against sounds coming from the street into the house. This research is a case study research, using a field survey method. The type of gate studied is the cangkem frog type which has a free yard and is located on the collector road. Data was obtained through direct observation and measurement using a sound level meter to determine the results of field measurements. This research shows that choosing the design and location of gates and tension walls as well as adding gates can reduce traffic noise by 5 to 13 dB.